Federative Republic of Brazil iRAP Pilot Technical Report : Federal Highways - World Bank (World Bank, Washington, DC, 2016)
As part of efforts to curb road deaths and serious injuries, the World Bank Global Road Safety Facility (GRSF) invited the International Road Assessment Programme (iRAP) to work with the National Department of Transport Infrastructure (Departamento Nacional de Infraestrutura de Transportes, DNIT) to assess the safety of Brazilian roads. During this second assessment of Brazilian roads, approximately 3,400km of roads were assessed. This technical report describes the road assessment project and includes details on data collection, the methodology used and a summary of the results. The infrastructure-related risk assessment involved detailed surveys and coding of 50 road attributes at 100 meter intervals along the network and creation of Star Ratings, which provide a simple and objective measure showing the level of risk on the road network. The star ratings show that 1 percent of road length is rated as 5-star, 9 percent is rated as 4-star, 58 percent is rated as 3-star, and the remaining 32 percent is rated as 2-star and below for vehicle occupants. For motorcyclists, no roads were rated as 5-star, only 3 percent of road length is rated as 4-star, 47 percent is rated as 3-star, and the remaining 50 percent is rated 2-star and below. For pedestrians less than 1 percent is rated as 4-star and 5-star, 2 percent is rated as 3-star and the remaining 13 percent is rated 2-star and below. For bicyclists less than 1 percent is rated as 5-star or 4-star, 5 percent is rated as 3-star and the remaining 14 percent is rated 2-star and below. The project also involved the creation of a Safer Roads Investment Plans, which draws on more than 90 proven road safety treatments, ranging from low cost road markings and pedestrian refuges to higher cost intersection upgrades and full highway duplication.